Effects of Polyamide Microplastic Particles on Aquatic Outdoor Ecosystems - A Mesocosm Study - Kruckenfellner, Lukas; Justus Liebig University Giessen (My University, 2026)
The protection and preservation of ecosystems, their biodiversity and the inherent ecosystem services should be a central goal of current scientific efforts. Not only the increasing chemical pollution, but also the increased occurrence of plastic is putting constant stress on ecosystems and individuals. There are many regulations and standardized procedures to assess the potential risk that chemical substances can have on the environment. This is not the case for particles such as microplastic. Although the uptake and transfer of microplastic particles along the food chain has already been proven, it is difficult to obtain a comparative overview of the ecotoxicological risk due to the large number of different parent substances, sizes, shapes and chemical additives. Standing water bodies such as lakes or reservoirs are a potential sink for such particles due to the lack of hydrodynamic pressure. This can lead to strong accumulations compared to the lotic inflows. The plastic particles, some of which are colonized by biofilms, can be mistaken for food or ingested unselectively by the organisms. This leads potentially to biomagnification in natural systems.
Since this can only be inadequately reproduced in classical laboratory studies, an aquatic field model ecosystem study was carried out in this project to investigate the influence of polyamide particles on aquatic biocoenosis. Particles with a size range of 5-50 µm were applied to the model ecosystems in three concentrations four times over a period of ten days in order to simulate a continuous influx of particles. In addition, a particulate control was used in the experiment to compare the potential effects of pure particles with those of the polyamide microplastic. Abiotic parameters and representatives of all trophic levels were regularly sampled and evaluated over a period of more than 100 days. The primary producers were represented by the chlorophyll a content in free-floating algae and the consumers and decomposers by animal plankton and larger invertebrates. The concentrations used in the approximately 1000 L systems were 1.5 mg L⁻¹, 15 mg L⁻¹ and 150 mg L⁻¹. In addition to pure abundance counts, the biovolume of adult and larval macroinvertebrates was also recorded and emergence time was established as a new endpoint for higher-tier studies.
The analysis of the samples revealed effects on the abundance of seed shrimps (Ostracoda). All polyamide treatments showed significant reductions compared to the control, with the effects at the highest concentration being the most long-term. No effects were observed in the particle control. A significantly earlier Emergence mean Time was observed in the emerged individuals of a subfamily of non-biting midges (Orthocladiinae). With a duration of 114 days this study is one of few to include long exposure, a particulate treated control and an environmentally realistic concentration of polyamide particles and gives important information for the risk assessment of microplastic under near-natural conditions.
Keywords: ddc:570